Strategi Pemerintah Daerah Kabupaten Tegal Dalam Meningkatkan Investasi Daerah Tahun 2015-2016 - Bimmo Faizal Risky; Muhammad Adnan (Journal of Politic and Government Studies, 2017)
This study was conducted to elucidate the strategies undertaken by local governments to increase investment Tegal regency for the year 2015-2016 which are reviewed areas of social, political, administrative, and economic as well as its resistance. In autonomous regions, all regions in Indonesia allowed to arrange their own affairs, including matters concerning investment.This study used a qualitative approach is further supported by primary data obtained from the District Government Tegal regency and secondary data obtained from books, reports, journals, internet, newspaper. The data collection techniques using interviews and document study.The results showed that a social strategy that is done to increase investment is to routinely dissemination to the public in the regions 'troubled' about the importance of investment, political strategy is to maintain political stability, strategies administrative done is cut licensing regulations, the economic strategy is to create competent labor  but the salary is not too high.Keyword : Strategy to Increase Investment, Local Investment and Increasing Investment